Spatial behavior of mesocarnivores living in seasonal ecosystems: A case study in arid landscapes in northern-central Chile - Darío Moreira-Arce; Pablo M. Vergara; Alex Oporto; Alberto J. Alaniz; Claudia Hidalgo-Corrotea; Alfredo H. Zúñiga; Alejo Gutiérrez; Sebastián Moreno; Daniela Araya; Simone Ciuti (Global Ecology and Conservation)
Understanding the habitat selection and movement patterns of carnivores in arid landscapes requires an assessment of the spatiotemporal patterns of ephemeral resource-rich and climatically suitable sites. One example is the South American grey fox (Lycalopex griseus), a mesocarnivore that inhabits north-central Chile, an arid region under increasing human presence and where coastal fog is an important but variable source of moisture. Here, we hypothesized that space use decisions of foxes are influenced by spatiotemporal variation in plant productivity, human settlements, and microclimate conditions. Home ranges and Resource Selection Functions were fitted to the GPS data of seven foxes tracked year-round and related to ecological landscape and site-level attributes derived from remote sensing. Home ranges increased with incident radiation, elevation, topographic diversity, normalized difference water index (ndwi), and distance to roads, but decreased with proximity to the coastline. Foxes avoided using sites distant from the coast, located at the highest altitudes, and with higher surface temperatures, while being more likely to move to sites with high ndwi. Our results show that South American grey foxes living in arid landscapes adjust their home ranges, and habitat use decisions within home ranges, to topography but also to environmental conditions that vary intra annually. Extreme microclimate conditions can directly shape the habitat use patterns but also indirectly through seasonally modifying plant productivity, while terrain morphology (topography and elevation) acts as a regulator of extreme climate. We also noted that road network influences the behavioral response of foxes and its expansion is expected to exert pressure on the conservation of fox populations.